Solid-phase Synthesis of Tetrapeptide on 2-Chlorotrityl Chloride Resin by Using Benzotriazol-1-yl-oxytripyrrolidinophosphonium Hexafluorophosphate as Coupling Reagent - Rani Maharani; Nuruzzahra Ammatillah; Gunawan Gunawan; Ace Tatang Hidayat (Jurnal Kimia Valensi, 2016)
Tetrapeptide, OH-Pro-Ala-Gly-Tyr-NH2, was successfully synthesised on 2-chlorotrityl chloride resin by taking advantage of PyBOP (benzotriazol-1-yl-oxytripyrrolidinophosphonium hexafluorophosphate) as coupling reagent. The selection of the peptide as the target of synthesis was due to its interesting bioactivity as antioxidant. The synthesis was undertaken with Fmoc strategy, where Fmoc-proline was added onto the resin at the first place. It is known from the literature that proline can resist from rasemisation when  it was attached on the resin at the first time. Fmoc deprotection step was carried out by employing 20% piperidine in DMF and the reaction mixture was shaken for 30 minutes. Once the proline attached, the next step was to attach amino acids, alanine (Ala), glycine (Gly) and tyrosine(Tyr), subsequently onto the resin until tetrapeptidyl resin was constructed on the resin.  Hydroxyl group of Tyr was protected with t-butyl, which is TFA-labiled. Coupling reaction was undertaken by mixing the amino acid and PyBOP in a mixture of dichloromethane and DMF (1:1) and in the presence of basic DIPEA. Resin cleavage step was carried out by using 95% TFA in water, where t-butyl protecting group on the side chain of Tyr was cleaved at the same time. The analytical RP-HPLC of the final product showed a single peak at 21.9 minutes (20-90% of acetonitrile in water with 0.1% of TFA during 30 minutes), indicating that each coupling has given a good coupling performance and resulting in a pure product. The desired product showed the correct molecular weight with m/z 407.2 [M+H]+ and 429.2 [M+Na]. DOI: http://dx.doi.org/10.15408/jkv.v0i0.4055